2022
DOI: 10.1021/acs.nanolett.2c00945
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Effect of *CO Coverage on C–C Coupling toward CO2 Electroreduction

Abstract: Cu-based tandem nanocrystals have been widely applied to produce multicarbon (C 2+ ) products via enhancing CO intermediate (*CO) coverage toward CO 2 electroreduction. Nevertheless, it remains ambiguous to understand the intrinsic correlation between *CO coverage and C−C coupling. Herein, we constructed a tandem catalyst via coupling CoPc with the gas diffusion electrode of Cu (GDE of Cu−CoPc). A faradaic efficiency for C 2+ products of 82% was achieved over a GDE of Cu−CoPc at an applied current density of 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
47
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(47 citation statements)
references
References 51 publications
0
47
0
Order By: Relevance
“…23,24 The stronger *CO adsorption may lead to the high coverage of *CO, thus decreasing the reaction energies of C−C coupling (Figure S1b,c). 24,25 Besides, the adsorption energy of *COH also increases with the decreased CNs.…”
mentioning
confidence: 99%
“…23,24 The stronger *CO adsorption may lead to the high coverage of *CO, thus decreasing the reaction energies of C−C coupling (Figure S1b,c). 24,25 Besides, the adsorption energy of *COH also increases with the decreased CNs.…”
mentioning
confidence: 99%
“…Recent studies have suggested that CO-producing molecular catalysts are alternative candidates to metals in tandem schemes. [25][26][27] Molecular components offer additional versatility compared to metals because their electronic and structural features can be tuned via synthetic modications. [28][29][30][31] While the examples are still limited, studies in the literature on tandem catalysts including CO-producing molecular catalysts and Cu are encouraging.…”
Section: Introductionmentioning
confidence: 99%
“…[28][29][30][31] While the examples are still limited, studies in the literature on tandem catalysts including CO-producing molecular catalysts and Cu are encouraging. [25][26][27] For example, the addition of either an iron porphyrin or a cobalt phthalocyanine to sputtered Cu resulted in enhanced C 2+ product yields. 25,26 Specically, the coupling of iron porphyrin with sputtered Cu resulted in increased faradaic efficiency for ethanol from 29% to 41% and in a shi the detection potential of this product from −0.84 to −0.82 V vs. RHE.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The electroreduction of CO 2 , driven by renewable electricity, paves a promising avenue to converting CO 2 into value-added chemicals and feedstocks for reducing the net CO 2 emission. Until recently, many kinds of products, such as carbon monoxide (CO), formate (HCOO – ), methane (CH 4 ), ethylene (C 2 H 4 ), ethanol (C 2 H 5 OH), and acetate (CH 3 COO – ), have been obtained during CO 2 electroreduction. Among all the carbonaceous products derived from CO 2 electroreduction, multicarbon (C 2+ ) products have drawn incredible attention as a result of the high energy density and unique chemical functional groups. At present, Cu-based materials are considered to be the most promising catalysts for producing C 2+ products because of the moderate binding of reaction intermediates on the surface of Cu. , Hence, it is of great importance to develop highly efficient Cu-based catalysts for improving the activity of C 2+ products.…”
mentioning
confidence: 99%